ACCUMULATION OF HEAVY METALS WITHIN HARD CORAL Porites lutea IN SPERMONDE ARCHIPELAGO, SOUTH SULAWESI - Samawi, Muhammad Farid; Werorilangi, Shinta; Tambaru, Rahmadi; Rastina, Rastina (Jurnal Ilmu Kelautan SPERMONDE, 2018)
Hard coral Porites lutea is an animal that lives on the ocean floor. This species may live for years and accumulate heavy metals from its surrounding environments. The aims of this study was to know accumulation of heavy metals (Pb, Cd, and Cu) pollution by Porites lutea at different islands in Spermonde Archipelago waters. This study used field surveys around Laelae, Bonebatang and Badi Islands of South Sulawesi. Field parameters measured were oceanographic parameters, metals in water and sediment. Hard coral was extracted using nitric acid, then measured its heavy metal levels using Atomic Absorption Spectrophotometer. Several field parameters such as temperature, salinity, turbidity, pH and dissolved oxygen indicated no differences at each location, whereas the difference was observed in the values of Total Suspended Solid and dissolved oxygen. The results showed the accumulation of heavy metals in the skeleton of Porites lutea was Pb>Cu>Cd and Laelae>Bonebatang>Badi Island.